Conchocarpus piranii (Galipeinae, Rutaceae), a new species from Eastern Brazil, with notes on its palynology, foliar and flower anatomy, and phylogenetic position - Groppo, Milton; Fabro, André Davanso; Maeoka, Heloísa Midori; Nogueira, Fernanda Mayara; Dutra, Fernanda Vitorete; Gasparino, Eduardo Custódio; Ferreira, Paola Lima; Miranda, Marcelo Dias; Afonso, Laura Fernandes (Phytotaxa, 2026)
Conchocarpus piranii (tribe Galipeeae, Rutaceae), a new species within the Neotropical subtribe Galipeinae, is described and illustrated. The new species occurs within the coastal forest vegetation of the Brazilian Atlantic Forest domain. Morphologically, Conchocarpus piranii is most like to other species of the genus with inflorescences bearing foliaceous bracts such as C. bellus. C. cuneifolius, and C. macrophyllus, but differs from them by its non-umbilicate ovary with a terminal style, whereas the other species exhibit an umbilicate ovary. Our DNA based phylogenetic analysis revealed that species with foliaceous inflorescences within Conchocarpus are not closely related to each other. Additional data on foliar and floral anatomy, as well as palynology, are provided, along with comments on the geographic distribution and conservation status of C. piranii.